An investigation into heterogeneity in a single vein-type uranium ore deposit: Implications for nuclear forensics. (December 2015) - Keatley, A.C.; Scott, T.B.; Davis, S.; Jones, C.P.; Turner, P.
Abstract: Minor element composition and rare earth element (REE) concentrations in nuclear materials are important as they are used within the field of nuclear forensics as an indicator of sample origin. However recent studies into uranium ores and uranium ore concentrates (UOCs) have shown significant elemental and isotopic heterogeneity from a single mine site such that some sites have shown higher variation within the mine site than that seen between multiple sites. The elemental composition of both uranium and gangue minerals within ore samples taken along a single mineral vein in South West England have been measured and reported here. The analysis of the samples was undertaken to determine the extent of the localised variation in key elements. Energy Dispersive X-ray spectroscopy (EDS) was used to analyse the gangue mineralogy and measure major element composition. Minor element composition and rare earth element (REE) concentrations were measured by Electron Probe Microanalysis (EPMA). The results confirm that a number of key elements, REE concentrations and patterns used for origin location do show significant variation within mine. Furthermore significant variation is also visible on a meter scale. In addition three separate uranium phases were identified within the vein which indicates multiple uranium mineralisation events. In light of these localised elemental variations it is recommended that representative sampling for an area is undertaken prior to establishing the REE pattern that may be used to identify the originating mine for an unknown ore sample and prior to investigating impact of ore processing on any arising REE patterns. Highlights: Demonstrating significant variation at meter scale distances. Importance of understanding heterogeneity in aid of nuclear forensics interpretation. Understanding local features prior to determining feed through of elements to UOCs. Key elements, REE concentrations and patterns show significant variation at a meter scale. Understanding the complications of representative sampling.